An alphavirus-derived self-amplifying mRNA encoding PpSP15-LmSTI1 fusion protein for the design of a vaccine against leishmaniasis. (August 2022) - Savar, Nastaran Sadat; Shengjuler, Djoshkun; Doroudian, Fatemeh; Vallet, Thomas; Mac Kain, Alice; Arashkia, Arash; Khamesipour, Ali; Lundstrom, Kenneth; Vignuzzi, Marco; Niknam, Hamid Mahmoudzadeh
Abstract: The main aims of the present study were to design a fusion protein of Leishmania major stress-inducible protein 1 (LmSTI1) and Phlebotomus papatasi SP15 (PpSP15), and to express it in the form of alphavirus packaged Self-amplifying mRNA (SAM). Two combinations, PpSP15-LmSTI1 and LmSTI1-PpSP15 fusion forms, were analyzed for folding and minimum free energies of the mRNA. Conformational studies on 3D modeled fusion and native forms were performed, and the Root-Mean-Square-distance (RMSD) of the Cα atomic coordinates were calculated. Antigenicity and stability were predicted using bioinformatics tools. The coding sequences of PpSP15-LmSTI1 fusion, PpSP15, and LmSTI1 were cloned into an alphavirus-based vector and used to produce the SAM constructs. All the subcloned constructs were then subjected to packaging in the form of viral replicon particles (VRPs), and were evaluated for their ability to infect BHK-21 cells and express the recombinant fusion proteins. The in-silico analysis indicated that the PpSP15-LmSTI1 combination could be a promising candidate based on lower folding ΔG of mRNA, higher protein antigenicity and lower instability indexes, and less conformational changes compared to the native proteins and the LmSTI1-PpSP15 fusion form. Packaged SAM encoding fusion and native antigens are used for infection of mammalian cells and for recombinant protein expression. This is the first study on in silico designing and successful packaging of an alphavirus-derived SAM in the form of the VRPs to target leishmaniasis. Highlights: PpSP15-LmSTI1 fusion could be a promising candidate for use in an alphavirus derived SAM-based vaccine against leishmaniasis. The SAM encoding PpSP15-LmSTI1 fusion protein can be transcribed, transfected and packaged in the viral replicon particles. TheSAM-based vaccines in form of the replicon particles can infect the host cells leading to the expression of the antigens.